Comparison of three interventions in the treatment of malnutrition in hospitalised older adults: A clinical trial. Issue 4 (29th January 2013) - Campbell, Katrina L.; Webb, Lindsey; Vivanti, Angela; Varghese, Paul; Ferguson, Maree
Abstract Aim The objective of the present study was to determine the most effective method for providing oral nutrition support to hospitalised older adult patients with malnutrition using clinical and patient‐centred measures. Methods The present study involved consecutive assignment of 98 inpatients assessed as malnourished (Subjective Global Assessment B or C) to conventional commercial supplements (traditional, n = 33), MedPass (n = 32, 2 cal/mL supplement delivered 60 mL four times a day at medication rounds) or mid‐meal trolley (n = 33, selective snack trolley offered between meals) for two weeks. Weight change, supplement compliance, energy and protein intake (3‐day food records), quality of life (EQ‐5D), patient satisfaction and cost were evaluated. Results Weight change was similar across the three interventions (mean ± SD): 0.4 ± 3.8% traditional; 1.5 ± 5.8% MedPass; 1.0 ± 3.1% mid‐meal (P = 0.53). Energy and protein intakes (% of requirements) were more often achieved with traditional (107 ± 26, 128 ± 35%) and MedPass (110 ± 28, 126 ± 38%) compared with mid‐meal (85 ± 25, 88 ± 25%) interventions (P = < 0.01). Overall quality‐of‐life ratings (scale 0–100) improved significantly with MedPass (mean change, 12.4 ± 20.9) and mid‐meal (21.1 ± 19.7) interventions, however, did not change with traditional intervention (1.5 ± 18.1) (P = 0.05). Patient satisfaction including sensory qualities (taste, look, temperature, size) and perceived benefit (improved health and recovery) was rated highest for mid‐meal trolley (all P < 0.05). Conclusions Patients achieved recommended intake with supplements (MedPass or traditional), and despite lower cost, higher satisfaction and quality of life with selective mid‐meal trolley did not achieve recommended energy and protein intake. Future research is warranted for implementing a combination of strategies in providing oral nutrition support.